2020
DOI: 10.1097/qco.0000000000000682
|View full text |Cite
|
Sign up to set email alerts
|

Unresolved issues in the identification and treatment of carbapenem-resistant Gram-negative organisms

Abstract: Purpose of review Carbapenem-resistant organisms (CROs), including Pseudomonas aeruginosa, Acinetobacter baumannii and Enterobacterales, are a threat worldwide. This review will cover mechanisms of resistance within CROs and challenges with identification and treatment of these organisms while pointing out unresolved issues and ongoing challenges. Recent findings The treatment of CROs has expanded through newer therapeutic options. Guided utilization th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…One of the strategies for managing CRO infections is to use the existing antibiotics wisely and rationally to improve clinical efficacy and meanwhile reduce adverse events. For example, polymyxins are often used in combination with tigecycline (TGC) or carbapenems to treat CRO infections (7)(8)(9)(10), even though randomized controlled trials (RCTs) have confirmed that colistin/meropenem or colistin/rifampicin combinations are not superior to colistin alone in the treatment of carbapenemresistant Gram-negative bacilli or drug-resistant A. baumannii (11,12). However, only a few clinical studies have been conducted on polymyxin B/TGC (PMB/TGC) combination in treating CRO infections (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…One of the strategies for managing CRO infections is to use the existing antibiotics wisely and rationally to improve clinical efficacy and meanwhile reduce adverse events. For example, polymyxins are often used in combination with tigecycline (TGC) or carbapenems to treat CRO infections (7)(8)(9)(10), even though randomized controlled trials (RCTs) have confirmed that colistin/meropenem or colistin/rifampicin combinations are not superior to colistin alone in the treatment of carbapenemresistant Gram-negative bacilli or drug-resistant A. baumannii (11,12). However, only a few clinical studies have been conducted on polymyxin B/TGC (PMB/TGC) combination in treating CRO infections (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Carbapenem-resistant Gram-negative bacilli (CR-GNB) are a threat worldwide. Carbapenem-resistant Enterobacterales (CRE), carbapenem-resistant Pseudomonas aeruginosa (CRPA), and carbapenem-resistant Acinetobacter baumannii (CRA) are considered as carbapenem-resistant organisms (CROs) [ 5 ]. Enterobacterales is an order of Gram-negative bacteria, comprising seven families and more than 80 genera.…”
Section: Introductionmentioning
confidence: 99%
“…GNB isolates testing resistant to any one of the Carbapenem group of antimicrobials (Ertapenem [only for CRE], Meropenem, Imipenem, Doripenem) were labelled as CR-GNB. 9 CFDC susceptibility testing of the CR-GNB isolates was performed by both reference BMD as well as DD. The study was approved by the institutional ethics committee of All India Institute of Medical Sciences [AIIMS], Bhubaneswar, Odisha (Ref Number: IEC/AIIMS BBSR/PG-Thesis/2019-20/100 dated 14th December 2019).…”
Section: Methodsmentioning
confidence: 99%